2022
DOI: 10.3390/rs14122897
|View full text |Cite
|
Sign up to set email alerts
|

Landslide Deformation Extraction from Terrestrial Laser Scanning Data with Weighted Least Squares Regularization Iteration Solution

Abstract: The extraction of landslide deformation using terrestrial laser scanning (TLS) has many important applications. The landslide deformation can be extracted based on a digital terrain model (DTM). However, such methods usually suffer from the ill-posed problem of a multiplicative error model as illustrated in previous studies. Moreover, the edge drift of commonly used spherical targets for point cloud registration (PCR) is ignored in the existing method, which will result in the unstable precision of the PCR. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Following the analysis presented in Section 4.2, it was determined that the landslides within the Lashagou landslide group, with the exception of L8, were formed either during the construction of highway G310 (L3, L4, L5, and L6) or after its completion (L1, L2, L7, R1, and R2). Excavation conducted during the construction of the highway is widely acknowledged as a significant factor and an essential condition for the formation of the Lashagou landslide group (e.g., [10,24]). This excavation activity altered the original state of the stress equilibrium in the slope, thereby directly inducing slope deformation, as exemplified by the occurrence of landslide L6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the analysis presented in Section 4.2, it was determined that the landslides within the Lashagou landslide group, with the exception of L8, were formed either during the construction of highway G310 (L3, L4, L5, and L6) or after its completion (L1, L2, L7, R1, and R2). Excavation conducted during the construction of the highway is widely acknowledged as a significant factor and an essential condition for the formation of the Lashagou landslide group (e.g., [10,24]). This excavation activity altered the original state of the stress equilibrium in the slope, thereby directly inducing slope deformation, as exemplified by the occurrence of landslide L6.…”
Section: Discussionmentioning
confidence: 99%
“…The Lashagou landslide group is situated in the transitional zone between the Qinghai-Tibet Plateau and the Loess Plateau (Figure 1a). Its primary cause of formation is considered to be the hillslope excavation activities conducted during the construction of the highway G310 from 2011 to 2013 [10,24]. However, no studies have yet demonstrated the impact of the construction of the highway G310 on the formation and evolution of the Lashagou landslide group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also does not need to touch the landslide body [42]. Consequently, numerous studies these days focus on using TLS for monitoring landslides [43][44][45][46][47][48]. However, this method also has some disadvantages, including a high volume of generated point clouds, especially for large areas, and the problem of accurately registering these point clouds.…”
Section: Terrestrial Laser Scannersmentioning
confidence: 99%
“…The iterative nearest point (ICP) algorithm is the most commonly applied PCR method because the iteration is simple, and the convergence speed is fast [11][12][13][14]. It iteratively calculates the optimum transformation until the function criterion converges to the specified value.…”
Section: Introductionmentioning
confidence: 99%